Composite copper foil and preparation method thereof

By forming a connecting layer and a catalytic layer on the substrate and combining electrochemical plating and electroplating technology to prepare composite copper foils, the problems of poor uniformity of copper layer and perforation of base film in the existing process are solved, and more efficient and reliable composite copper foil production is achieved.

CN117845201BActive Publication Date: 2025-03-14JIANG SU WEI LAI XIANG SU KE JI YOU XIAN GONG SI +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410008798.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2025-03-14
Estimated Expiration
2044-01-03

Smart Images

  • Figure CN117845201B_ABST
    Figure CN117845201B_ABST
Patent Text Reader

Abstract

The invention discloses a composite copper foil and a preparation method thereof, and relates to the technical field of composite materials. The preparation method of the composite copper foil comprises the following steps: S1. providing a substrate; S2. coating a first liquid on one side or both sides of the substrate, drying, and forming a connecting layer, wherein the first liquid comprises an EVA emulsion, a branched acrylate emulsion, an adhesive, a defoaming agent, and a dispersant; S3. coating a second liquid on the surface of the connecting layer, drying, and forming a catalytic layer, wherein the second liquid comprises nano-metal particles; S4. forming a first copper film layer on the surface of the catalytic layer by chemical copper plating; in the present invention, the connecting layer can effectively improve the connection force between the substrate and the catalytic layer, the catalytic layer can efficiently improve the efficiency of chemical copper plating, and is conducive to improving the uniformity of the formed first copper film layer, and the preparation of the composite copper foil is more efficient and the cost is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper foil production, and in particular to a composite copper foil and a preparation method thereof. Background Art

[0002] Composite copper foil refers to a new type of material made by evenly plating copper on the surface of a plate by magnetron sputtering, evaporation, ion replacement, etc. Composite copper foil has good tensile strength, elongation, oxidation resistance, corrosion resistance and conductivity, and is widely used in lithium batteries, military shielding films, wireless communications, touch panels, touch conductive films, and energy storage fields and other components that use copper as a conductive carrier.

[0003] In the prior art, the magnetron sputtering method is mainly used to produce composite copper foil, or an electroplating process or vacuum evaporation method is added after the magnetron sputtering process to increase the copper thickness, so as to improve the conductive properties of the composite copper foil. However, the magnetron sputtering method needs to be carried out in a high temperature environment, which is easy to cause perforation of the base film, and further causes the copper foil to break during rolling. After the rolling is broken, nearly 20m of the material strip needs to be scrapped and it takes 15 minutes to manually connect the strips, which affects the yield and cost. Furthermore, after the composite copper foil with perforated base film is applied to the battery, the battery is prone to lithium deposition, which reduces the cycle life. The lithium dendrites formed by lithium deposition can easily cause the battery to short-circuit after piercing the diaphragm. Furthermore, the copper layer of the composite copper foil produced by magnetron sputtering deposition is poorly uniform and unevenly thick, which leads to an increase in the impedance of the lithium battery, thereby reducing the battery charging and discharging efficiency; in addition, in the prior art, the composite copper foil production process is complicated, the production yield is low, the output is low, the investment is large, and it is difficult to mass-produce on a large scale.

[0004] Therefore, it is necessary to improve the prior art to overcome the above defects in the prior art. Summary of the invention

[0005] The object of the present invention is to provide a composite copper foil and a preparation method thereof, which can efficiently prepare the composite copper foil and is beneficial to improving the uniformity of the copper layer.

[0006] To achieve the above-mentioned object of the invention, the present invention proposes a method for preparing a composite copper foil, comprising the following steps:

[0007] S1. Provide a substrate;

[0008] S2. Coating a first liquid on one or both sides of the substrate surface and drying to form a connecting layer, wherein the first liquid comprises an EVA emulsion, a branched acrylate emulsion, a binder, a defoamer and a dispersant;

[0009] S3. Coating a second liquid on the surface of the connecting layer and drying it to form a catalytic layer, wherein the second liquid includes nano-metal particles;

[0010] S4. Forming a first copper film layer on the surface of the catalyst layer by chemical copper plating.

[0011] Furthermore, the first liquid also includes a barrier filler. The first liquid includes, by weight, 10 to 50 parts of EVA emulsion, 10 to 30 parts of branched acrylate emulsion, 1 to 10 parts of barrier filler, 1 to 10 parts of binder, 0.5 to 1 part of defoamer, and 0.1 to 0.5 part of dispersant.

[0012] Furthermore, the solid content of the EVA emulsion is 50% to 60%;

[0013] The branched acrylic ester emulsion is prepared by adding 0.1 to 10 parts by weight of azobisisobutyronitrile and 3 to 10 parts by weight of a polyether crosslinking agent to a total of 10 to 30 parts by weight of acrylic acid and / or methyl acrylate and / or ethyl acrylate;

[0014] The barrier filler is a surface-modified hetero-nitrogen silicon compound;

[0015] The binder is rosin resin;

[0016] The defoamer is any one of the organosilicon defoamers;

[0017] The dispersant is a BYK series dispersant.

[0018] Furthermore, the first liquid is prepared by the following steps:

[0019] A1. A mixture of one or more of acrylic acid, methyl acrylate and ethyl acrylate is stirred uniformly, nitrogen is passed for 5 to 20 min, the system temperature is raised to 70 to 80 ° C, azobisisobutyronitrile is added, and the reaction is carried out for 4 to 8 hours to obtain a branched acrylate emulsion;

[0020] A2. The EVA emulsion, the branched acrylic emulsion and the barrier agent are mixed uniformly to obtain a premixed solution;

[0021] A3. Add the binder and defoamer into the premixed liquid and stir to obtain the first liquid.

[0022] Furthermore, in the step S2, the first liquid is coated on the surface of the substrate by roller coating, spin coating or slit coating;

[0023] In step S2, the drying temperature is 70-90°C and the drying time is 0.5-3 min;

[0024] In the step S3, the second liquid is coated on the surface of the connecting layer by roller coating, spin coating or slit coating;

[0025] In step S3, the drying temperature is 70-90° C., and the drying time is 0.5-3 min.

[0026] Furthermore, the second liquid includes a metal ion solution, a reducing agent, a dispersant, a surfactant and deionized water, and the metal ion solution includes one or more ions of palladium, copper, silver, nickel, tin, zinc or gold ions.

[0027] Furthermore, the second liquid comprises, by weight, 1 to 5 parts of the metal ion solution, 10 to 20 parts of the reducing agent, 0.01 to 0.05 parts of the dispersant, 0.1 to 0.5 parts of the surfactant, and 20 to 80 parts of the deionized water;

[0028] The metal ion solution is a palladium salt, and the palladium salt is a mixture of one or more of palladium sulfate, palladium chloride and palladium acetate;

[0029] The reducing agent is a mixture of one or more of ethyl acetate, ethyl formate and ethylene glycol amine;

[0030] The dispersant is solsperse 44000 or solsperse 46000 or a mixture of the two;

[0031] The surfactant is a fluorosilicone surfactant.

[0032] Further, the second liquid comprises, by weight, 0.1 to 0.3 parts of the metal ion solution, 5 to 10 parts of the dispersant, 100 to 150 parts of the reducing agent, 1 to 10 parts of the surfactant and 200 to 500 parts of the deionized water;

[0033] The metal ion solution is a silver salt, and the silver salt is silver nitrate or silver perchlorate or a mixture of the two;

[0034] The reducing agent is a mixture of one or more of glucose, hydrazine hydrate, glycerol and triethanolamine;

[0035] The dispersant is polyvinyl pyrrolidone or polyethylene glycol or a mixture of the two;

[0036] The surfactant is Chemours FS-3000 or Chemours FS-3100 or a mixture of the two.

[0037] Furthermore, the second liquid is prepared by the following steps:

[0038] B1. Take the metal ion solution and add it to the reducing agent, stir evenly to obtain a pre-mixed liquid;

[0039] B2. adding the dispersant and the surfactant to the stirred liquid, stirring, and heating under reflux at a temperature of 80 to 150 ° C for 0.5 to 3 h;

[0040] B3. After the liquid obtained in step B2 is cooled, the deionized water is added at a rotation speed of 200 to 800 rpm to obtain the second liquid.

[0041] Furthermore, in step S4, the chemical copper plating comprises the following steps:

[0042] The substrate having the catalyst layer and the connecting layer is contacted with a chemical copper plating solution, wherein the temperature of the chemical copper plating solution is 30 to 50° C. and the contact time is 2 to 8 minutes;

[0043] The chemical copper plating solution is prepared by the following steps:

[0044] C1. Add 70 to 80 parts by weight of deionized water into the plating tank;

[0045] C2. The internal circulation stirring of the chemical plating tank is turned on, and 2 to 5 parts by weight of a copper salt solution is added, wherein the copper salt solution is a mixture of one or more of anhydrous copper sulfate, copper chloride or copper nitrate;

[0046] C3. Adding 5 to 10 parts by weight of the complexing agent to the solution obtained in step C2, wherein the complexing agent is EDTA or sodium tartrate;

[0047] C4. adding 1 to 5 parts by weight of a pH regulator and 1 to 5 parts by weight of a reducing agent to the solution obtained in step C3, wherein the pH regulator is a sodium hydroxide solution or a potassium hydroxide solution or a mixture of the two, and the reducing agent is a formaldehyde solution;

[0048] C5. Add 0.1 to 0.5 parts by weight of the stabilizer to the liquid obtained in step C4 to obtain the chemical copper plating solution, wherein the stabilizer is thiourea, potassium thiocyanate, mercaptobenzothiazole, phenanthroline or 2,2-bipyridine.

[0049] Furthermore, the method for preparing the composite copper foil further comprises the following steps:

[0050] S5. Forming a second copper film layer on the surface of the first copper film layer by electroplating;

[0051] In step S5, electroplating includes the following steps:

[0052] The substrate with the first copper film layer, the catalyst layer and the connecting layer obtained in step S4 is immersed in an electroplating solution at an electroplating temperature of 20 to 40° C. for a time of 1 to 10 minutes;

[0053] The electroplating solution comprises, by weight, 10 to 25 parts of copper salt, 60 to 70 parts of acidic electrolyte, 0.1 to 2 parts of brightener, 0.1 to 0.5 parts of inhibitor and 10 to 20 parts of deionized water;

[0054] The copper salt is a mixed solution of one or more of copper sulfate, copper chloride, copper nitrate, copper phosphate and copper pyrophosphate;

[0055] The acidic electrolyte is a mixture of one or more of sulfuric acid, hydrochloric acid, nitric acid, formic acid, acetic acid, phosphoric acid and sulfonic acid;

[0056] The inhibitor is a mixture of one or more of polyether substances, epoxy copolymers and ketone substances;

[0057] The brightener is one or a mixture of 2-hydroxy-3-mercapto sodium sulfonate, 4-phenylimidazole and 2-benzylimidazolinium.

[0058] Further, the material of the substrate is one or more combinations of polyethylene terephthalate, polyethylene naphthalate, cellulose acetate, alicyclic hydrocarbons, polymethyl methacrylate, polyimide, biaxially oriented polypropylene, polypropylene, polycarbonate, copolymers and blends; or,

[0059] The substrate is made of glass, flexible glass or quartz.

[0060] In addition, the present invention also provides a composite copper foil, which is prepared by the composite copper foil preparation method as described in any one of the above items;

[0061] The composite copper foil comprises a substrate, a connecting layer is arranged on one or both sides of the substrate, a catalytic layer is arranged on the surface of the connecting layer, a first copper film layer is arranged on the surface of the catalytic layer, and a second copper film layer is arranged on the surface of the first copper film layer.

[0062] Compared with the prior art, the present invention has the following beneficial effects: the preparation method of the composite copper foil of the present invention forms a connecting layer by coating and drying on a substrate, forms a catalytic layer by coating and drying, and then forms a first copper film layer by chemical copper plating. The connecting layer can effectively improve the connection between the substrate and the catalytic layer, the catalytic layer can efficiently improve the efficiency of chemical copper plating, and is beneficial to improving the uniformity of the formed first copper film layer. The obtained copper film is more uniform than the copper film obtained by magnetron sputtering. Moreover, the entire preparation method does not need to use magnetron sputtering, evaporation and the like, can efficiently prepare composite copper foil, has lower cost, is not prone to problems such as rolling breakage caused by substrate perforation, and when it is applied to lithium batteries, it can effectively reduce the risk of lithium plating, thereby improving the service life and reliability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 It is a cross-sectional view of a composite copper foil according to an embodiment of the present invention.

[0064] Figure 2 It is a cross-sectional view of a composite copper foil according to an embodiment of the present invention.

[0065] Figure 3 The present invention is a flow chart of a method for preparing a composite copper foil according to an embodiment of the present invention.

[0066] Figure 4 The present invention is a flowchart of preparing a first liquid according to an embodiment of the present invention.

[0067] Figure 5 The present invention is a flowchart of preparing the second liquid according to an embodiment of the present invention.

[0068] Figure 6 The present invention is a flow chart of preparing a chemical copper plating solution according to an embodiment of the present invention. DETAILED DESCRIPTION

[0069] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0070] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0071] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0072] like Figures 1 to 3 As shown, a method for preparing a composite copper foil corresponding to a preferred embodiment of the present invention includes the following steps.

[0073] S1. Provide a substrate 1.

[0074] In some embodiments, the material of the substrate 1 is a combination of one or more of polyethylene terephthalate, polyethylene naphthalate, cellulose acetate, alicyclic hydrocarbons, polymethyl methacrylate, polyimide, bi-axially oriented polypropylene, polypropylene, and polycarbonate. The substrate 1 made of the above materials has good toughness; in other embodiments, the substrate 1 can be any other transparent material suitable for use as a touch sensor substrate, for example, made of transparent materials such as glass, flexible glass, or quartz; the material of the substrate 1 can be selected according to the application scenario of the composite copper foil.

[0075] S2. Coating a first liquid on one or both sides of the substrate 1 and drying the first liquid to form a connecting layer 2, wherein the first liquid includes EVA emulsion, branched acrylate emulsion, adhesive, defoamer and dispersant.

[0076] S3. Coating a second liquid on the surface of the connecting layer 2 and drying it to form a catalytic layer 3, wherein the second liquid includes nano-metal particles.

[0077] In step S3, the first liquid serves as a primer liquid for enhancing the surface adhesion of the substrate 1. The connecting layer 2 formed by the first liquid has good adhesion to both the substrate 1 and the catalytic layer 3, can improve the adhesion strength between the catalytic layer 3 and the substrate 1, and has good acid and alkali resistance, corrosion resistance and high temperature resistance.

[0078] S4. Forming a first copper film layer 4 on the surface of the catalyst layer 3 by chemical copper plating, that is, forming the first copper film layer 4 by reacting a chemical copper plating solution with the catalyst layer 3 .

[0079] In step S4 , since the catalyst layer 3 includes metal particles, the metal particles play a catalytic role in the chemical copper plating, which can improve the efficiency of the chemical copper plating and catalyze the copper ions to form the first copper film layer 4 more effectively.

[0080] The preparation method of the above-mentioned composite copper foil forms a connecting layer by coating and drying on a substrate, forms a catalytic layer by coating and drying, and then forms a first copper film layer by chemical copper plating. The connecting layer can effectively improve the connection force between the catalytic layer and the catalytic layer can efficiently improve the efficiency of chemical copper plating, and is beneficial to improve the uniformity of the formed first copper film layer. The obtained copper film is more uniform than the copper film obtained by magnetron sputtering. Moreover, the entire preparation method does not require the use of magnetron sputtering, evaporation and the like, and can efficiently prepare composite copper foil with lower cost. It is not easy to have problems such as rolling breakage caused by substrate perforation. When it is applied to lithium batteries, it can effectively reduce the risk of lithium plating, thereby improving the service life and reliability of the battery.

[0081] In some embodiments, the first liquid in step S2 includes, by weight, 10 to 50 parts of EVA emulsion, 10 to 30 parts of branched acrylate emulsion, 1 to 10 parts of binder, 0.5 to 1 part of defoamer, and 0.1 to 0.5 parts of dispersant. Optionally, the first liquid also includes a barrier filler, by weight, the first liquid also includes 1 to 10 parts by weight of the barrier filler, which can improve the adhesion and thickening properties during mixing.

[0082] As an example, the first liquid may include 10 parts of EVA emulsion, 10 parts of branched acrylic emulsion, 1 part of barrier filler, 1 part of binder, 0.5 part of defoamer, and 0.1 part of dispersant; as another example, 50 parts of EVA emulsion, 30 parts of branched acrylic emulsion, 10 parts of barrier filler, 10 parts of binder, 1 part of defoamer, and 0.5 part of dispersant; as yet another example, 25 parts of EVA emulsion, 15 parts of branched acrylic emulsion, 5 parts of barrier filler, 5 parts of binder, 0.7 part of defoamer, and 0.3 part of dispersant.

[0083] Further optionally, the solid content of the above EVA emulsion is 50% to 60% (the solid content is the mass percentage of the remaining part of the emulsion or coating after drying under specified conditions).

[0084] Optionally, the branched acrylic ester emulsion is prepared by adding 0.1-10 parts by weight of azobisisobutyronitrile and 3-10 parts by weight of a polyether crosslinking agent to 10-30 parts by weight of acrylic acid, methyl acrylate or ethyl acrylate, and reacting them under certain conditions; the barrier filler is a surface-modified heteroazo silicon compound, for example, it can be surface-modified heteroazocyclic attapulgite, and the binder is a rosin resin; the defoamer is any one of the silicone defoamers; and the dispersant is a BYK series dispersant.

[0085] In some embodiments, the first liquid can be prepared by the following steps.

[0086] A1. A mixture of one or more of acrylic acid, methyl acrylate and ethyl acrylate is stirred uniformly, nitrogen is passed through for 5 to 20 minutes, the system temperature is raised to 70 to 80°C, azobisisobutyronitrile is added, and the reaction is carried out for 4 to 8 hours to obtain a branched acrylate emulsion.

[0087] In step A1, for example, acrylic acid and hydroxymethyl acrylate may be uniformly mixed to prepare a branched acrylic ester emulsion.

[0088] A2. Evenly mix the EVA emulsion, the branched acrylic emulsion and the barrier filler to obtain a premixed solution.

[0089] A3. Add the binder and defoamer into the premixed liquid and stir to obtain the first liquid.

[0090] In step S2, the first liquid can be coated on the surface of the substrate 1 by roller coating, spin coating or slit coating, and then dried, and a uniform connection layer 2 can be obtained in this way. Optionally, the drying temperature of the first liquid is 70 to 90°C, and the drying time is 0.5 to 3 minutes. After drying, the connection layer 2 is obtained, for example, by drying in a high-temperature oven. Optionally, the thickness of the connection layer 2 is 20 to 200 nm.

[0091] In some embodiments, the second liquid includes a metal ion solution, a reducing agent, a dispersant, a surfactant, and deionized water, and the metal ion solution includes one or more ions of palladium, copper, silver, nickel, tin, zinc, or gold ions.

[0092] In some embodiments, the metal ion solution is a palladium salt, and the second liquid includes, by weight, 1 to 5 parts by weight of the metal ion solution, 10 to 20 parts by weight of a reducing agent, 0.01 to 0.05 parts by weight of a dispersant, 0.1 to 0.5 parts by weight of a surfactant, and 20 to 80 parts by weight of deionized water.

[0093] As an example, the weight portion of the palladium salt metal ion solution is 1 part, the weight portion of the reducing agent is 10 parts, the weight portion of the dispersant is 0.01 parts, the weight portion of the surfactant is 0.1 parts, and the weight portion of deionized water is 20 parts. As another example, the weight portion of the metal ion solution is 5 parts, the weight portion of the reducing agent is 20 parts, the weight portion of the dispersant is 0.05 parts, the weight portion of the surfactant is 0.5 parts, and the weight portion of the deionized water is 80 parts. As another example, the weight portion of the metal ion solution is 3 parts, the weight portion of the reducing agent is 15 parts, the weight portion of the dispersant is 0.03 parts, the weight portion of the surfactant is 0.3 parts, and the weight portion of the deionized water is 50 parts.

[0094] As an example, the palladium salt is a mixture of one or more of palladium sulfate, palladium chloride and palladium acetate; the reducing agent is a mixture of one or more of ethyl acetate, ethyl formate and ethylene glycolamine; the dispersant is solsperse 44000 or solsperse 46000 or a mixture of the two; and the surfactant is a fluorosilicone surfactant.

[0095] The above materials are heated and refluxed to prepare an aqueous nano-palladium catalyst solution, in which the particle size of the precious metal nano-palladium is relatively small, ranging from 20 to 400 nm, and has high catalytic activity and stability.

[0096] In some embodiments, the metal ion solution is a silver salt, and the second liquid includes, by weight, 0.1 to 0.3 parts of the metal ion solution, 5 to 10 parts of the dispersant, 100 to 150 parts of the reducing agent, 1 to 10 parts of the surfactant and 200 to 500 parts of the deionized water.

[0097] As an example, the weight part of the silver salt metal ion solution is 0.1 parts, the weight part of the dispersant is 5 parts, the weight part of the reducing agent is 100 parts, the weight part of the surfactant is 1 part, and the weight part of deionized water is 200 parts; as another example, the weight part of the silver salt metal ion solution is 0.3 parts, the weight part of the dispersant is 10 parts, the weight part of the reducing agent is 150 parts, the weight part of the surfactant is 10 parts, and the weight part of deionized water is 500 parts; as another example, the weight part of the silver salt metal ion solution is 0.2 parts, the weight part of the dispersant is 7 parts, the weight part of the reducing agent is 130 parts, the weight part of the surfactant is 7 parts, and the weight part of deionized water is 300 parts.

[0098] As an example, the silver salt is silver nitrate or silver perchlorate or a mixture of the two; the reducing agent is a mixture of one or more of glucose, hydrazine hydrate, glycerol and triethanolamine; the dispersant is polyvinyl pyrrolidone (PVP) or polyethylene glycol or a mixture of the two; the surfactant is Chemours FS-3000 or Chemours FS-3100 or a mixture of the two. Preferably, the concentration (wt%) of glucose is 40%.

[0099] Optionally, the second liquid is prepared by the following steps.

[0100] B1. Add the metal ion solution to the reducing agent and stir evenly to obtain a pre-stirred solution.

[0101] B2. Add the dispersant and surfactant to the stirring liquid, stir, and reflux heat at 80-150°C for 0.5-3h.

[0102] B3. After the liquid obtained in step B2 is cooled, deionized water is added at a rotation speed of 200 to 800 rpm to obtain a second liquid.

[0103] In step S3, the second liquid can be coated on the surface of the connecting layer 2 by roller coating, spin coating or slit coating. Optionally, the second liquid is dried at a temperature of 70 to 90°C for 0.5 to 3 minutes, and a catalyst layer 3 having a thickness of about 20 to 200 nm is obtained after drying.

[0104] In some embodiments, the chemical copper plating in step S4 includes the following steps.

[0105] The substrate 1 formed with the catalyst layer 3 and the connecting layer 2 is contacted with a chemical copper plating solution, for example, it can be directly immersed in the chemical copper plating solution, or passed through a chemical solution tank in a roll-to-roll manner. The temperature of the chemical copper plating solution is 30-50°C, and the contact time is 2-8 minutes. A first copper film layer 4 with a thickness of about 100-1000 nm is formed on the surface of the catalyst layer 3.

[0106] In some embodiments, the chemical copper plating solution may include, by weight, 70 to 80 parts by weight of deionized water, 2 to 5 parts by weight of a copper salt (e.g., a mixture of one or more of anhydrous copper sulfate, copper chloride or copper nitrate), 1 to 5 parts by weight of a reducing agent (e.g., a formaldehyde solution), 1 to 5 parts by weight of a pH regulator (e.g., a sodium hydroxide or potassium hydroxide solution or a mixture of the two), 5 to 10 parts by weight of a complexing agent (e.g., EDTA or sodium tartrate), and 0.1 to 0.5 parts by weight of a stabilizer (e.g., thiourea, potassium thiocyanate, mercaptobenzothiazole, phenanthroline or 2,2-bipyridine).

[0107] As an example, the chemical copper plating solution includes 80 parts by weight of deionized water, 5 parts by weight of copper salt solution, 5 parts by weight of reducing agent, 5 parts by weight of PH adjusting agent, 10 parts by weight of complexing agent, and 0.5 parts by weight of stabilizer. As another example, the chemical copper plating solution includes 70 parts by weight of deionized water, 2 parts by weight of copper salt solution, 2 parts by weight of reducing agent, 2 parts by weight of PH adjusting agent, 5 parts by weight of complexing agent, and 0.5 parts by weight of stabilizer. As another example, the chemical copper plating solution includes 75 parts by weight of deionized water, 3 parts by weight of copper salt solution, 3 parts by weight of reducing agent, 3 parts by weight of PH adjusting agent, 7 parts by weight of complexing agent, and 0.25 parts by weight of stabilizer.

[0108] Further optionally, the chemical copper plating solution is prepared by the following steps.

[0109] C1. Add 70 to 80 parts by weight of deionized water into the chemical plating tank.

[0110] C2. Start the internal circulation stirring of the chemical plating tank, and add 2 to 5 parts by weight of copper salt solution, which is a mixture of one or more of anhydrous copper sulfate, copper chloride or copper nitrate.

[0111] C3. Add 5 to 10 parts by weight of a complexing agent to the solution obtained in step C2, wherein the complexing agent is EDTA or sodium tartrate, or a mixture of the two.

[0112] C4. Add 1 to 5 parts by weight of a pH adjusting liquid and 1 to 5 parts by weight of a reducing agent to the solution obtained in step C3, wherein the pH adjusting agent is a sodium hydroxide or potassium hydroxide solution, and the reducing agent is a formaldehyde solution.

[0113] C5. Add 0.1 to 0.5 parts by weight of a stabilizer to the liquid obtained in step C4 to obtain a chemical copper plating solution. Optionally, the stabilizer is thiourea, potassium thiocyanate, mercaptobenzothiazole, phenanthroline or 2,2-bipyridine.

[0114] In some embodiments, the following step is further included after step S4: S5. Forming a second copper film layer 5 on the surface of the first copper film layer 4 by electroplating.

[0115] In step S5, copper ions in the electroplating solution are reduced to copper atoms through electrode reaction when electricity is applied, and are deposited on the first copper film layer 4 to form a second copper film layer 5. The thickness of the copper layer of the composite copper foil can be increased by electroplating, thereby improving the overall conductivity.

[0116] In some embodiments, the electroplating in step S5 includes the following steps:

[0117] The substrate 1 with the first copper film layer 4, the catalyst layer 3 and the connecting layer 2 prepared in step S4 is immersed in an electroplating solution, the electroplating temperature is 20-40°C, and the electroplating time is 1-10 minutes. The electroplating method adopts a stepwise DC density increasing method, and the current density can be 1ASD, 1.2ASD, 1.4ASD, 1.6ASD, 1.8ASD and 2ASD.

[0118] Furthermore, the electroplating solution includes, by weight, 10 to 25 parts of copper salt, 60 to 70 parts of acidic electrolyte, 0.1 to 2 parts of brightener and 0.1 to 0.5 parts of inhibitor, and 10 to 20 parts of deionized water.

[0119] As an example, the electroplating solution includes 10 parts by weight of copper salt, 60 parts by weight of acidic electrolyte, 0.1 parts by weight of brightener, 0.1 parts by weight of inhibitor and 10 parts by weight of deionized water. As another example, the electroplating solution includes 25 parts by weight of copper salt, 70 parts by weight of acidic electrolyte, 2 parts by weight of brightener, 0.5 parts by weight of inhibitor and 20 parts by weight of deionized water. As another example, the electroplating solution includes 17 parts by weight of copper salt, 65 parts by weight of acidic electrolyte, 1 part by weight of brightener, 0.25 parts by weight of inhibitor and 15 parts by weight of deionized water.

[0120] Optionally, the copper salt is a mixture of one or more of copper sulfate, copper chloride, copper nitrate, copper phosphate and copper pyrophosphate; the acidic electrolyte is a mixture of one or more of sulfuric acid, hydrochloric acid, nitric acid, formic acid, acetic acid, phosphoric acid and sulfonic acid; the inhibitor is a mixture of one or more of polyether substances, epoxy copolymers and ketone substances; the brightener is a mixture of one or more of 2-hydroxy-3-mercapto sodium sulfoxide, 4-phenylimidazole and 2-benzylimidazolinone.

[0121] Optionally, the thickness of the second copper film layer obtained by electroplating is in the range of 0.5 to 10 μm.

[0122] Example 1

[0123] 1) The first liquid is coated on the surface of the substrate 1 by roller coating, and then dried in a high-temperature oven at 70° C. for 3 minutes to obtain a connecting layer 2.

[0124] Wherein, the first liquid is prepared by the following method:

[0125] a. Mix 10 parts by weight of acrylic acid and hydroxymethyl acrylate evenly, pass nitrogen for 5 minutes, raise the system temperature to 70°C, add 0.1 parts by weight of azobisisobutyronitrile and 3 parts by weight of polyether crosslinking agent, react for 8 hours to obtain a branched acrylic ester emulsion; b. Put 10 parts by weight of EVA emulsion, 10 parts by weight of branched acrylic ester emulsion and 1 part by weight of barrier filler (azirogenated silicon compound) into a stirrer and mix evenly to obtain a premixed liquid; c. Add 1 part by weight of rosin resin binder, 0.5 parts by weight of silicone defoamer and 0.1 parts by weight of BYK series dispersant to the premixed liquid and stir to obtain a first liquid;

[0126] 2) The second liquid is applied to the surface of the connecting layer 2 by roller coating, and then dried in a high-temperature oven at 70° C. for 3 minutes to obtain a catalytic layer 3;

[0127] The preparation method of the second liquid is as follows: a. 1 part by weight of palladium sulfate is added to 10 parts by weight of ethyl acetate solution, and stirred at 200 rpm for 1 hour; b. 0.01 parts by weight of dispersant and 0.1 parts by weight of surfactant are added to the stirred liquid, and refluxed at 80° C. for 2 hours, wherein the dispersant is solsperse 44000, and the surfactant is FC series of fluorosilicone surfactant produced by 3M Company; c. After the liquid is cooled, 20 parts by weight of deionized water is added at 200 rpm to obtain the second liquid;

[0128] 3) The substrate 1 having the connection layer 2 and the catalyst layer 3 prepared by coating is immersed in a chemical copper plating solution. The temperature of the chemical copper plating solution is 30° C. and the chemical copper plating time is 8 minutes.

[0129] The preparation method of the chemical copper plating solution is as follows: a. adding 70 parts by weight of deionized water into the chemical plating tank; b. starting the internal circulation stirring of the chemical plating tank, and adding 2 parts by weight of a copper salt solution, wherein the copper salt is anhydrous copper sulfate; c. adding 5 parts by weight of a complexing agent into the above solution, wherein the complexing agent is EDTA; d. adding 1 part by weight of a sodium hydroxide solution as a pH regulating liquid and 1 part by weight of a formaldehyde solution as a reducing agent into the above solution; e. adding 0.1 parts by weight of a stabilizer into the above liquid, wherein the stabilizer is thiourea.

[0130] 4) The substrate 1 having the first copper film layer 4 obtained by chemical plating is immersed in an electroplating solution at an electroplating temperature of 20°C, an electroplating time of 10 minutes, and a current density of 1 ASD. The electroplating solution comprises the following components: 10 parts by weight of a copper salt, which is copper nitrate; 60 parts by weight of an acidic electrolyte, which is sulfuric acid; 0.1 parts by weight of a brightener, which is sodium 2-hydroxy-3-mercaptosulfurate; 0.1 parts by weight of an inhibitor, which is a polyether substance; and 10 parts by weight of deionized water.

[0131] Example 2

[0132] 1) The first liquid is applied to the surface of the substrate 1 by spin coating, and then dried in a high-temperature oven at 90° C. for 0.5 min to obtain a connecting layer 2.

[0133] Wherein, the first liquid is prepared by the following method:

[0134] a. Stir 30 parts by weight of acrylic acid evenly, pass nitrogen for 20 minutes, raise the system temperature to 80°C, add 10 parts by weight of azobisisobutyronitrile and 10 parts by weight of a polyether crosslinking agent, react for 4 hours to obtain a branched acrylic ester emulsion; b. Put 50 parts by weight of EVA emulsion, 30 parts by weight of branched acrylic ester emulsion and 10 parts by weight of barrier filler (azirogenated silicon compound) into a stirrer, mix evenly to obtain a premixed liquid; c. Add 10 parts by weight of rosin resin binder, 1 part by weight of silicone defoamer and 0.5 parts by weight of BYK series dispersant to the premixed liquid, stir to obtain a first liquid;

[0135] 2) Spin coating the second liquid onto the surface of the connecting layer 2, and drying it in a high-temperature oven at 90° C. for 0.5 min to obtain a catalytic layer 3;

[0136] The preparation method of the second liquid is as follows: a. 5 parts by weight of palladium chloride is added to 20 parts by weight of ethyl formate solution, and stirred at 380 rpm for 4 hours; b. 0.01 parts by weight of a dispersant and 0.5 parts by weight of a surfactant are added to the stirred liquid, and refluxed at 120° C. for 2 hours, wherein the dispersant is solsperse 46000, and the surfactant is a fluorosilicone surfactant FC series produced by 3M Company; c. After the liquid is cooled, 80 parts of deionized water are added at 800 rpm to obtain the second liquid;

[0137] 3) The substrate 1 having the connection layer 2 and the catalyst layer 3 prepared by coating is immersed in a chemical copper plating solution. The temperature of the chemical copper plating solution is 50° C. and the chemical copper plating time is 8 minutes.

[0138] The preparation method of the chemical copper plating solution is as follows: a. adding 80 parts by weight of deionized water into the chemical plating tank; b. starting the internal circulation stirring of the chemical plating tank, and adding 5 parts by weight of a copper salt solution, wherein the copper salt is copper chloride; c. adding 10 parts by weight of a complexing agent into the above solution, wherein the complexing agent is sodium tartrate; d. adding 5 parts by weight of a potassium hydroxide solution as a pH regulating liquid and 5 parts by weight of a formaldehyde solution as a reducing agent into the above solution; e. adding 0.5 parts by weight of a stabilizer into the above liquid, wherein the stabilizer is potassium thiocyanate.

[0139] 4) The substrate 1 having the first copper film layer obtained by chemical plating is immersed in an electroplating solution at an electroplating temperature of 40°C, an electroplating time of 1 min, and a current density of 2 ASD. The electroplating solution comprises the following components: 25 parts by weight of a copper salt, which is copper phosphate; 70 parts by weight of an acidic electrolyte, which is phosphoric acid; 2 parts by weight of a brightener, which is 4-phenylimidazole; 0.5 parts by weight of an inhibitor, which is an epoxy copolymer; and 20 parts by weight of deionized water.

[0140] Example 3

[0141] 1) The first liquid is coated on the surface of the substrate 1 by slit coating, and then dried in a high-temperature oven at 80° C. for 2 minutes to obtain a connecting layer 2.

[0142] Wherein, the first liquid is prepared by the following method:

[0143] a. Mix a total of 15 parts by weight of acrylic acid, methyl acrylate and ethyl acrylate, pass nitrogen for 5 minutes, raise the system temperature to 75°C, add 5 parts by weight of azobisisobutyronitrile and 7 parts by weight of a polyether crosslinking agent, react for 6 hours to obtain a branched acrylic ester emulsion; b. Put 30 parts by weight of EVA emulsion, 20 parts by weight of branched acrylic ester emulsion and 5 parts by weight of barrier filler (azirogenated silicon compound) into a stirrer and mix well to obtain a premixed liquid; c. Add 5 parts by weight of rosin resin binder, 0.7 parts by weight of silicone defoamer and 0.3 parts by weight of BYK series dispersant to the premixed liquid and stir to obtain a first liquid;

[0144] 2) The second liquid is coated on the surface of the connecting layer 2 by slit coating, and then dried in a high-temperature oven at 80° C. for 2 minutes to obtain a catalytic layer 3;

[0145] The preparation method of the second liquid is as follows: a. 3 parts by weight of palladium acetate is added to 15 parts by weight of ethylene glycol amine solution, and stirred at 380 rpm for 3 hours; b. 0.03 parts by weight of a dispersant and 0.3 parts by weight of a surfactant are added to the stirred liquid, and refluxed at 100° C. for 2 hours, wherein the dispersant is solsperse 44000, and the surfactant is a fluorosilicone surfactant FC series produced by 3M Company; c. After the liquid is cooled, 50 parts by weight of deionized water is added at 500 rpm to obtain the second liquid;

[0146] 3) The substrate 1 having the connection layer 2 and the catalyst layer 3 prepared by coating is immersed in a chemical copper plating solution, the temperature of the chemical copper plating solution is 40° C., and the chemical copper plating time is 5 minutes.

[0147] The preparation method of the chemical copper plating solution is as follows: a. adding 75 parts by weight of deionized water into the chemical plating tank; b. starting the internal circulation stirring of the chemical plating tank, and adding 3 parts by weight of a copper salt solution, wherein the copper salt is copper nitrate; c. adding 8 parts by weight of a complexing agent into the above solution, wherein the complexing agent is EDTA; d. adding 3 parts by weight of a sodium hydroxide solution as a pH regulating liquid and 3 parts by weight of a formaldehyde solution as a reducing agent into the above solution; e. adding 0.3 parts by weight of a stabilizer into the above liquid, wherein the stabilizer is 2,2-bipyridine.

[0148] 4) The substrate 1 having the first copper film layer obtained by chemical plating is immersed in an electroplating solution at an electroplating temperature of 30°C, an electroplating time of 5 minutes, and a current density of 1.6 ASD. The electroplating solution comprises the following components: 18 parts by weight of a copper salt, which is copper pyrophosphate; 65 parts by weight of an acidic electrolyte, which is hydrochloric acid; 1 part by weight of a brightener, which is 2-benzyl imidazoline; 0.3 parts by weight of an inhibitor, which is a ketone substance; and 15 parts by weight of deionized water.

[0149] Example 4

[0150] 1) The first liquid is coated on the surface of the substrate 1 by slit coating, and then dried in a high-temperature oven at 75° C. for 2 minutes to obtain a connecting layer 2.

[0151] Wherein, the first liquid is prepared by the following method:

[0152] a. Mix 25 parts by weight of methyl acrylate and ethyl acrylate uniformly, pass nitrogen for 18 minutes, raise the system temperature to 78°C, add 7 parts by weight of azobisisobutyronitrile and 8 parts by weight of a polyether crosslinking agent, react for 6 hours to obtain a branched acrylate emulsion; b. Put 40 parts by weight of EVA emulsion, 25 parts by weight of branched acrylate emulsion and 5 parts by weight of barrier filler (azirogenated silicon compound) into a stirrer and mix uniformly to obtain a premixed liquid; c. Add 7 parts by weight of rosin resin binder, 0.9 parts by weight of silicone defoamer and 0.4 parts by weight of BYK series dispersant to the premixed liquid and stir to obtain a first liquid;

[0153] 2) The second liquid is coated on the surface of the connecting layer 2 by slit coating, and then dried in a high-temperature oven at 85° C. for 1 min to obtain a catalytic layer 3;

[0154] The preparation method of the second liquid is as follows: a. taking 0.1 parts by weight of silver nitrate solution, 5 parts by weight of dispersant and 1 part by weight of surfactant, adding them to 100 parts by weight of reducing agent and stirring evenly, wherein the dispersant is polyvinyl pyrrolidone (PVP) and the reducing agent is glucose (concentration 40%); b. reflux heating at a temperature of 100° C. for 3 hours; c. after the above liquid is cooled, adding 200 parts by weight of deionized water at a speed of 300 rpm to obtain the second liquid;

[0155] 3) The substrate 1 having the connection layer 2 and the catalyst layer 3 prepared by coating is immersed in a chemical copper plating solution. The temperature of the chemical copper plating solution is 45° C. and the chemical copper plating time is 3 minutes.

[0156] The preparation method of the chemical copper plating solution is as follows: a. adding 77 parts by weight of deionized water into the chemical plating tank; b. starting the internal circulation stirring of the chemical plating tank, and adding 4 parts by weight of a copper salt solution, wherein the copper salt is an anhydrous copper sulfate solution; c. adding 8 parts by weight of a complexing agent into the above solution, wherein the complexing agent is EDTA; d. adding 4 parts by weight of a sodium hydroxide solution as a pH regulating liquid and 4 parts by weight of a formaldehyde solution as a reducing agent into the above solution; e. adding 0.4 parts by weight of a stabilizer into the above liquid, wherein the stabilizer is mercaptobenzothiazole.

[0157] 4) The substrate 1 having the first copper film layer obtained by chemical plating is immersed in an electroplating solution at an electroplating temperature of 35°C, an electroplating time of 3 minutes, and a current density of 2ASD. The electroplating solution comprises the following components: 20 parts by weight of a copper salt, which is copper phosphate; 68 parts by weight of an acidic electrolyte, which is sulfonic acid; 1.5 parts by weight of a brightener, which is 2-benzyl imidazoline; 0.4 parts by weight of an inhibitor, which is a ketone substance; and 18 parts by weight of deionized water.

[0158] Example 5

[0159] 1) The first liquid is coated on the surface of the substrate 1 by roller coating, and then dried in a high-temperature oven at 85° C. for 1 min to obtain a connecting layer 2.

[0160] Wherein, the first liquid is prepared by the following method:

[0161] a. Mix 15 parts by weight of ethyl acrylate evenly, pass nitrogen for 13 minutes, raise the system temperature to 75°C, add 3 parts by weight of azobisisobutyronitrile and 5 parts by weight of a polyether crosslinking agent, react for 5 hours to obtain a branched acrylate emulsion; b. Put 20 parts by weight of EVA emulsion, 15 parts by weight of branched acrylate emulsion and 3 parts by weight of barrier filler (azirogenated silicon compound) into a stirrer and mix evenly to obtain a premixed liquid; c. Add 3 parts by weight of rosin resin binder, 0.6 parts by weight of silicone defoamer and 0.2 parts by weight of BYK series dispersant to the premixed liquid and stir to obtain a first liquid;

[0162] 2) Spin coating the second liquid onto the surface of the connecting layer 2, and drying it in a high-temperature oven at 75° C. for 2 minutes to obtain a catalytic layer 3;

[0163] The preparation method of the second liquid is as follows: a. taking 0.3 parts by weight of silver perchlorate solution, 10 parts by weight of a dispersant and 10 parts by weight of a surfactant, adding them to 150 parts by weight of a reducing agent and stirring them evenly, wherein the dispersant is polyethylene glycol and the reducing agent is hydrazine hydrate; b. reflux heating at a temperature of 150° C. for 0.5 hours; c. after the above liquid is cooled, adding 500 parts by weight of deionized water at a speed of 600 rpm to obtain the second liquid;

[0164] 3) The substrate 1 having the connection layer 2 and the catalyst layer 3 prepared by coating is immersed in a chemical copper plating solution. The temperature of the chemical copper plating solution is 35° C. and the chemical copper plating time is 6 minutes.

[0165] The preparation method of the chemical copper plating solution is as follows: a. adding 73 parts by weight of deionized water into the chemical plating tank; b. starting the internal circulation stirring of the chemical plating tank, and adding 3 parts by weight of a copper salt solution, wherein the copper salt is copper chloride; c. adding 6 parts by weight of a complexing agent into the above solution, wherein the complexing agent is EDTA; d. adding 2 parts by weight of a sodium hydroxide solution as a pH regulating liquid and 2 parts by weight of a formaldehyde solution as a reducing agent into the above solution; e. adding 0.2 parts by weight of a stabilizer into the above liquid, wherein the stabilizer is phenanthroline.

[0166] 4) The substrate 1 having the first copper film layer obtained by chemical plating is immersed in an electroplating solution at an electroplating temperature of 25° C., an electroplating time of 8 minutes, and a current density of 1 ASD. The electroplating solution comprises the following components: 15 parts by weight of a copper salt, which is copper chloride; 62 parts by weight of an acidic electrolyte, which is nitric acid; 1.2 parts by weight of a brightener, which is 2-hydroxy-3-mercaptosulfuric acid sodium; 0.2 parts by weight of an inhibitor, which is a polyether substance; and 13 parts by weight of deionized water.

[0167] Example 6

[0168] 1) The first liquid is applied to the surface of the substrate 1 by spin coating, and then dried in a high-temperature oven at 70° C. for 3 minutes to obtain a connecting layer 2.

[0169] Wherein, the first liquid is prepared by the following method:

[0170] a. Mix 20 parts by weight of methyl acrylate evenly, pass nitrogen for 15 minutes, raise the system temperature to 75°C, add 5 parts by weight of azobisisobutyronitrile and 5 parts by weight of polyether crosslinking agent, react for 5 hours to obtain a branched acrylate emulsion; b. Put 30 parts by weight of EVA emulsion, 20 parts by weight of branched acrylate emulsion and 6 parts by weight of barrier filler (azirogenated silicon compound) into a stirrer and mix evenly to obtain a premixed liquid; c. Add 3 parts by weight of rosin resin binder, 0.7 parts by weight of silicone defoamer and 0.3 parts by weight of BYK series dispersant to the premixed liquid and stir to obtain a first liquid;

[0171] 2) The second liquid is coated on the surface of the connecting layer 2 by slit coating, and then dried in a high-temperature oven at 80° C. for 2 minutes to obtain a catalytic layer 3;

[0172] The preparation method of the second liquid is as follows: a. taking 0.2 parts by weight of a mixed solution of silver perchlorate and nitrogen nitrate, 7 parts by weight of a dispersant and 7 parts by weight of a surfactant, adding them to 125 parts by weight of a reducing agent and stirring them evenly, wherein the dispersant is polyethylene glycol and the reducing agent is hydrazine hydrate; b. reflux heating at a temperature of 130° C. for 2 hours; c. after the above liquid is cooled, adding 300 parts by weight of deionized water at a speed of 500 rpm to obtain the second liquid;

[0173] 3) The substrate 1 having the connection layer 2 and the catalyst layer 3 prepared by coating is immersed in a chemical copper plating solution, the temperature of the chemical copper plating solution is 40° C., and the chemical copper plating time is 5 minutes.

[0174] The preparation method of the chemical copper plating solution is as follows: a. adding 75 parts by weight of deionized water into the chemical plating tank; b. starting the internal circulation stirring of the chemical plating tank, and adding 3 parts by weight of a copper salt solution, wherein the copper salt is copper nitrate; c. adding 7 parts by weight of a complexing agent into the above solution, wherein the complexing agent is EDTA; d. adding 3 parts by weight of a sodium hydroxide solution as a pH regulating liquid and 3 parts by weight of a formaldehyde solution as a reducing agent into the above solution; e. adding 0.3 parts by weight of a stabilizer into the above liquid, wherein the stabilizer is thiourea.

[0175] 4) The substrate 1 having the first copper film layer obtained by chemical plating is immersed in an electroplating solution at an electroplating temperature of 35°C, an electroplating time of 4 minutes, and a current density of 1.6 ASD. The electroplating solution comprises the following components: 20 parts by weight of a copper salt, which is copper chloride; 65 parts by weight of an acidic electrolyte, which is acetic acid; 1.5 parts by weight of a brightener, which is 4-phenylimidazole; 0.3 parts by weight of an inhibitor, which is an epoxy copolymer; and 15 parts by weight of deionized water.

[0176] The present invention also provides a composite copper foil, which is prepared by the composite copper foil preparation method as described above. The composite copper foil comprises a substrate 1, a catalyst layer 3 disposed on the surface of a connecting layer 2, a first copper film layer 4 disposed on the surface of the catalyst layer 3, and a second copper film layer 5 disposed on the surface of the first copper film layer 4.

[0177] It can be understood that in step S2, when the first liquid is applied only on one side of the substrate 1, the connecting layer 2 is formed on one side of the substrate 1, and subsequently the catalytic layer 3, the first copper film layer 4 and the second copper film layer 5 are also formed only on one side of the substrate 1, thereby forming Figure 1 When the first liquid is coated on both sides of the substrate 1, a connecting layer 2 is formed on both surfaces of the substrate 1, and then a catalytic layer 3, a first copper film layer 4 and a second copper film layer 5 are formed on both sides of the substrate 1, thereby forming a structure as shown. Figure 2 The structure shown.

[0178] The above are only specific embodiments of the present invention, and any other improvements made based on the concept of the present invention are considered to be within the protection scope of the present invention.

Claims

1. A method for preparing a composite copper foil, characterized in that: The steps include: S1. Providing a substrate (1); S2. coating a first liquid on one or both sides of the substrate (1), drying the liquid, and forming a connecting layer (2), wherein the first liquid comprises an EVA emulsion, a branched acrylic emulsion, a binder, a defoaming agent, and a dispersant, and the thickness of the connecting layer (2) is 20 to 200 nm, and the branched acrylic emulsion is prepared by adding 0.1 to 10 parts by weight of azobisisobutyronitrile and 3 to 10 parts by weight of a polyether crosslinking agent to a total of 10 to 30 parts by weight of acrylic acid and / or methyl acrylate and / or ethyl acrylate; S3. Coating a second liquid on the surface of the connecting layer (2) and drying to form a catalytic layer (3), wherein the second liquid comprises nano-metal particles, the second liquid comprises a metal ion solution, a reducing agent, a dispersant, a surfactant and deionized water, the nano-metal particles are generated by the reaction of the metal ion solution, the reducing agent, the dispersant, the surfactant and the deionized water, and the thickness of the catalytic layer (3) is 20-200 nm; wherein the metal ion solution is a palladium salt, and the second liquid comprises, by weight, 1-5 parts of the metal ion solution, 10-20 parts of the reducing agent, and 10-20 parts of the dispersant. 0.01 to 0.05 parts, 0.1 to 0.5 parts of the surfactant, 20 to 80 parts of the deionized water, the reducing agent is a mixture of one or more of ethyl acetate, ethyl formate and ethylene glycol amine; or, the metal ion solution is a silver salt, the second liquid comprises 0.1 to 0.3 parts of the metal ion solution, 5 to 10 parts of the dispersant, 100 to 150 parts of the reducing agent, 1 to 10 parts of the surfactant and 200 to 500 parts of the deionized water, the reducing agent is a mixture of one or more of glucose, hydrazine hydrate, glycerol and triethanolamine; S4. Forming a first copper film layer (4) on the surface of the catalyst layer (3) by chemical copper plating.

2. The method for preparing the composite copper foil according to claim 1, characterized in that: The first liquid also includes a barrier filler. The first liquid includes, by weight, 10 to 50 parts of EVA emulsion, 10 to 30 parts of branched acrylate emulsion, 1 to 10 parts of barrier filler, 1 to 10 parts of binder, 0.5 to 1 part of defoamer, and 0.1 to 0.5 part of dispersant.

3. The method for preparing the composite copper foil according to claim 2, characterized in that: The solid content of the EVA emulsion is 50% to 60%; The barrier filler is a surface-modified hetero-nitrogen silicon compound; The binder is rosin resin; The defoamer is any one of the organosilicon defoamers; The dispersant is a BYK series dispersant.

4. The method for preparing the composite copper foil according to claim 2, characterized in that: The first liquid is prepared by the following steps: A1. A mixture of one or more of acrylic acid, methyl acrylate and ethyl acrylate was stirred uniformly, nitrogen was passed for 5 to 20 min, the system temperature was raised to 70 to 80 ° C, azobisisobutyronitrile was added, and the reaction was carried out for 4 to 8 hours to obtain a branched acrylate emulsion; A2. The EVA emulsion, the branched acrylic emulsion and the barrier agent are mixed uniformly to obtain a premixed solution; A3. Add the binder and defoamer into the premixed liquid and stir to obtain the first liquid.

5. The method for preparing the composite copper foil according to claim 1, characterized in that: In the step S2, the first liquid is coated on the surface of the substrate (1) by roller coating, spin coating or slit coating; In step S2, the drying temperature is 70-90°C and the drying time is 0.5-3 min; In the step S3, the second liquid is coated on the surface of the connecting layer (2) by roller coating, spin coating or slit coating; In step S3, the drying temperature is 70-90° C., and the drying time is 0.5-3 min.

6. The method for preparing the composite copper foil according to claim 1, characterized in that: When the metal ion solution is a palladium salt, the palladium salt is a mixture of one or more of palladium sulfate, palladium chloride and palladium acetate; The dispersant is solsperse 44000 or solsperse 46000 or a mixture of the two; The surfactant is a fluorosilicone surfactant.

7. The method for preparing the composite copper foil according to claim 1, characterized in that: When the metal ion solution is a silver salt, the silver salt is silver nitrate or silver perchlorate or a mixture of the two; The dispersant is polyvinyl pyrrolidone or polyethylene glycol or a mixture of the two; The surfactant is Chemours FS-3000 or Chemours FS-3100 or a mixture of the two.

8. The method for preparing the composite copper foil according to claim 1, characterized in that: The second liquid is prepared by the following steps: B1. Take the metal ion solution and add it to the reducing agent, stir evenly to obtain a pre-mixed liquid; B2. adding the dispersant and the surfactant to the stirred liquid, stirring, and heating under reflux at a temperature of 80 to 150 ° C for 0.5 to 3 h; B3. After the liquid obtained in step B2 is cooled, the deionized water is added at a rotation speed of 200-800 rpm to obtain the second liquid.

9. The method for preparing the composite copper foil according to any one of claims 1 to 8, characterized in that: In step S4, chemical copper plating includes the following steps: The substrate (1) formed with the catalytic layer (3) and the connecting layer (2) is brought into contact with a chemical copper plating solution, wherein the temperature of the chemical copper plating solution is 30 to 50° C. and the contact time is 2 to 8 minutes; The chemical copper plating solution is prepared by the following steps: C1. Add 70 to 80 parts by weight of deionized water into the plating tank; C2. The internal circulation stirring of the chemical plating tank is turned on, and 2 to 5 parts by weight of a copper salt solution is added, wherein the copper salt solution is a mixture of one or more of anhydrous copper sulfate, copper chloride or copper nitrate; C3. Adding 5 to 10 parts by weight of a complexing agent to the solution obtained in step C2, wherein the complexing agent is EDTA or sodium tartrate; C4. adding 1 to 5 parts by weight of a pH regulator and 1 to 5 parts by weight of a reducing agent to the solution obtained in step C3, wherein the pH regulator is a sodium hydroxide solution or a potassium hydroxide solution or a mixture of the two, and the reducing agent is a formaldehyde solution; C5. Add 0.1 to 0.5 parts by weight of a stabilizer to the liquid obtained in step C4 to obtain the chemical copper plating solution, wherein the stabilizer is thiourea, potassium thiocyanate, mercaptobenzothiazole, phenanthroline or 2,2-bipyridine.

10. The method for preparing the composite copper foil according to any one of claims 1 to 8, characterized in that: It also includes the following steps: S5. forming a second copper film layer (5) on the surface of the first copper film layer (4) by electroplating; In step S5, electroplating includes the following steps: The substrate (1) with the first copper film layer (4), the catalytic layer (3) and the connecting layer (2) obtained in step S4 is immersed in an electroplating solution at an electroplating temperature of 20 to 40° C. and an electroplating time of 1 to 10 minutes; In parts by weight, the electroplating solution comprises 10 to 25 parts by weight of a copper salt, 60 to 70 parts by weight of an acidic electrolyte, 0.1 to 2 parts by weight of a brightener, 0.1 to 0.5 parts by weight of an inhibitor, and 10 to 20 parts by weight of deionized water; The copper salt is a mixed solution of one or more of copper sulfate, copper chloride, copper nitrate, copper phosphate and copper pyrophosphate; The acidic electrolyte is a mixture of one or more of sulfuric acid, hydrochloric acid, nitric acid, formic acid, acetic acid, phosphoric acid and sulfonic acid; The inhibitor is a mixture of one or more of polyether substances, epoxy copolymers and ketone substances; The brightener is one or a mixture of 2-hydroxy-3-mercaptosulfuric acid sodium, 4-phenylimidazole and 2-benzylimidazolinium.

11. The method for preparing a composite copper foil according to any one of claims 1 to 8, characterized in that: The material of the substrate is one or more combinations of polyethylene terephthalate, polyethylene naphthalate, cellulose acetate, alicyclic hydrocarbons, polymethyl methacrylate, polyimide, biaxially oriented polypropylene, polypropylene, polycarbonate, copolymers and blends; or, The material of the substrate (1) is glass, flexible glass or quartz.

12. A composite copper foil, characterized in that: Prepared by the preparation method of the composite copper foil according to any one of claims 1 to 11; The composite copper foil comprises a substrate (1), a connection layer (2) is provided on one or both sides of the substrate (1), a catalytic layer (3) is provided on the surface of the connection layer (2), a first copper film layer (4) is provided on the surface of the catalytic layer (3), and a second copper film layer (5) is provided on the surface of the first copper film layer (4).

Citation Information

Patent Citations

  • Flexible current collector, preparation method and application thereof

    CN115842086A

  • Copper-plated PP film primer for lithium battery electrode and pretreatment preparation process

    CN116694148A

  • Copper colloid catalyst liquid for electroless copper plating and electroless copper plating method

    JP2016151056A